Lippincott's Q & A Certification Review : Emergency Nursing. - Springhouse (Wolters Kluwer Health, 2004)
This comprehensive workbook is an indispensable aid for emergency room nurses preparing for the CEN exam. The book contains over 1,400 questions and answers in an easy-to-use two-column format-questions in the left column, correct answers and rationales in the right. A bound-in CD-ROM contains over 300 additional questions. Coverage encompasses all subject areas in the CEN exam blueprint, and includes 5-tier triage, ECG strips, long-term complications of ED care, disaster management, and recognition and emergency management of chemical and biological weapons of mass destruction. The book inclu.